An audit of burns mortality between November 2007 and June 2008 using mortuary injury data in Lusaka, Zambia. (7th October 2012) - Mtonga, R
Abstract : Summary: Lusaka, the Capital City of Zambia, runs a Death Registry Office, which captures all deaths in a catchment area of nearly 2 000 000 people before disposal of the body by burial or cremation. Objectives: To audit burns-related mortality between November 2007 and June 2009 at the Lusaka Death Registry. Methods: This was a retrospective study employing all records including Certificates of Deaths, Burial Permits and Postmortem findings. The data was then compared with originating Health centre and Police death Records. Results: A total of 614 injury-related deaths were recorded with 104 or 16.9% due to burns. The majority 78(75%) involved children under 6 years of age, 27(15%) aged 7–35 years while the rest 10(4%) were over 36 years old. 58(55.8%) were males and 46(44.2%) were female. Dry and wet heat, open fires, hot water, porridge, combustible agents such as petroleum products were the causative agents. Contribution to the Field: Burns mortality, a largely preventable cause of death in Lusaka, mainly affects children under 6 years of age. Clinician's early and prudent use of antibiotics, bactericidal creams, skin grafting, adequate rehydration and good nutrition can help prevent burns mortality. Studying and taking measures to reduce contact with causative agents will help reduce burns mortality and injury-related mortality overall. Death Registries can be used to not only to show burns mortality trends and causative agents but monitor effectiveness of treatment regimens.